2012
DOI: 10.4161/spmg.20220
|View full text |Cite
|
Sign up to set email alerts
|

Daily sperm production and evaluation of morphological reproductive parameters of Murrah buffaloes in an extensive breeding system

Abstract: The development of male sexual maturity varies among buffaloes. The Murrah buffalo is considered the most important and efficient milk and fat producer, but aspects of its reproductive biology are still unknown. The present study aimed to evaluate the daily sperm production (DSP) and spermatogenesis in developing Murrah buffalo bulls by evaluation of the seminiferous tubules, testicular morphometry and using light microscopy and scanning electron microscopy. The testes of Murrah buffalo bulls at 18 mo was imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The level of male reproductive function in mammals can be assessed by testis weight, total semen volume, sperm morphology, sperm concentration and sperm motility. It also been suggested that sperm head count can be an informative index of sperm production, as it corresponds to the number of elongated spermatids in testis (da Luz et al, 2012;França & Godinho, 2003). Studies have been conducted in rats, mice and rabbits using a similar design based upon mobile phone RF exposure for variable lengths of time (Kesari et al, 2010;Sarookhani et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The level of male reproductive function in mammals can be assessed by testis weight, total semen volume, sperm morphology, sperm concentration and sperm motility. It also been suggested that sperm head count can be an informative index of sperm production, as it corresponds to the number of elongated spermatids in testis (da Luz et al, 2012;França & Godinho, 2003). Studies have been conducted in rats, mice and rabbits using a similar design based upon mobile phone RF exposure for variable lengths of time (Kesari et al, 2010;Sarookhani et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…About 60 to 65% of mature body weight may be a standard during the starting breeding season in heifers (Endecott et al, 2013). Da Luz et al (2012) reported that Murrah buffalo reached sexual maturity at 2 year of age and at this time sperm production is 13 million sperm per gram of testis. The monthly weight gain was faster upto 3 month of age and slower from 3 to 6 month of age in case of swamp buffalo (Das, 2004) and Murrah buffalo.…”
Section: Growth and Body Weightmentioning
confidence: 99%
“…Similarly, delayed sexual maturity is a serious problem in male buffalo. Establishment of spermatogenesis in buffalo testis is delayed in comparison to cattle [5,6]. This delay in sexual maturation can be attributed to lower plasma testosterone level in male buffalo as compared to cattle [7,8].…”
Section: Introductionmentioning
confidence: 99%